STRATEGI PROMOSI OBJEK WISATA TAMAN HUTAN RAYA (TAHURA) DI KABUPATEN SUMEDANG - Ningrum, Dhesti Widya Nurhasanah; Sister, Willy Amalia; Susilawati, Sussy; Amida, Ringga; Yustira, Yusuf; Irawan, Hendi (LPPM UNSAP & FISIP UNSAP, 2024)
Tourism promotion is needed to introduce a product to the general public. The Sumedang Regency Regional Government as part of the regional tourist attraction manager must have a regional tourist attraction promotion strategy. Tahura in Sumedang Regency is part of a regional tourist attraction which is one of the regional income from the tourism sector. Therefore, it is necessary to develop a tourist attraction promotion strategy that can have an impact on increasing tourists to Tahura tourist attractions in Sumedang Regency. So that the purpose of this research is to analyze the promotion strategy of Tahura tourist attractions in Sumedang Regency. The method that researchers use is qualitative research methods. Qualitative research methods are defined as the steps used by researchers to solve problems and answer their research questions. The results showed that three of the four tourist attraction promotion strategies could not be implemented optimally by the Sumedang Regency Regional Government in carrying out Tahura promotion. The absence of promotional slogans and taglines, the lack of complete tourist attractions, and the absence of people marketing that helps promotion. The local government has so far only been able to provide good road access for tourists where road access is part of the marketing infrastructure. To be able to carry out image marketing, attraction marketing, and people marketing strategies, cooperation with the private sector is needed in formulating tourism development that focuses on developing the three promotional strategies.